Disruption of the lung-gut-brain axis is responsible for cortex damage induced by pulmonary exposure to zinc oxide nanoparticles. (February 2023) - Zhang, Lingbing; Zhang, Yandan; Jiang, Xuejun; Mao, Lejiao; Xia, Yinyin; Fan, Yinzhen; Li, Na; Jiang, Ziqi; Qin, Xia; Jiang, Yu; Liu, Gang; Qiu, Feng; et al.
Abstract: Increasing evidence shows that gut microbiota is important for host health in response to metal nanomaterials exposure. However, the effect of gut microbiota on the cortex damage caused by pulmonary exposure to zinc oxide nanoparticles (ZnONPs) remains mainly unknown. In this study, a total of 48 adult C57BL/6J mice were intratracheally instilled with 0.6 mg/kg ZnONPs in the presence or absence of antibiotics (ABX) treatment. Besides, 24 mice were treated with or without fecal microbiota transplantation (FMT) after the intraperitoneal administration of ABX. Our results demonstrated for the first time that dysbiosis induced by ABX treatment significantly aggravated cortex damage induced by pulmonary exposure to ZnONPs. Such damage might highly occur through the induction of oxidative stress, manifested by the enhancement of antioxidative enzymes and products of lipid peroxidation. However, ferroptosis was not involved in this process. Interestingly, our data revealed that ABX treatment exacerbated the alterations of gut-brain peptides (including Sst, Sstr2, and Htr4 ) induced by ZnONPs in both gut and cortex tissues. Moreover, fecal microbiota transplantation (FMT) was able to alleviate cerebral cortex damage, oxidative stress, and alterations of gut-brain peptides induced by pulmonary exposure to ZnONPs. The results together indicate that pulmonary exposure to ZnONPs causes cerebral cortex damage possibly via the disruption of the lung-gut-brain axis. These findings not only propose valuable insights into the mechanism of ZnONPs neurotoxicity but also provide a potential therapeutic method against brain disorders induced by pulmonary exposure to ZnONPs. Availability of data and materials: The datasets used and/or analyzed during the current study are available from the The corresponding author on reasonable request. Highlights: Dysbiosis in gut aggravated cortex damage induced by ZnONPs. Dysbiosis in gut aggravated oxidative stress induced by ZnONPs. Fecal microbiota transplantation alleviated cortex damage induced by ZnONPs. Dysbiosis in gut aggravated cortex damage regulated by gut-brain peptides. Dysbiosis in gut possibly aggravated cortex damage via the lung-gut-brain axis.